ANALISIS LITERASI SAINS PESERTA DIDIK SMPN 1 GRESIK - Indah Lailatul Rohmah; Siti Nurul Hidayati (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2021)
The results of this survey research aim to describe the level of achievement of students' scientific literacy. This research involved the research subjects of Grade 8 students of SMP Negeri 1 Gresik in the 2019/2020 Academic Year. The research sample was taken randomly from classes VIII F, VIII G, VIII H, VIII I, and VIII J. The data collection technique used a test instrument containing 15 scientific literacy questions, which were adopted from PISA questions and referred to several parameters for each aspect of scientific literacy. The test results were analyzed based on standard deviation and categorized into 3, namely: low, medium, and high categories. The results showed that the level of scientific literacy of 8th grade students of SMP Negeri 1 Gresik in the low category was 12%, the medium category was 68%, and the high category was 20%. As for the achievement of each indicator of scientific literacy, different percentages were obtained. The conclusions of this study indicate the tendency of the level of scientific literacy of students of SMP Negeri 1 Gresik to be in the medium category. The implication of the results of this study is that teachers can determine the level of scientific literacy of their students, so that they can design appropriate learning models and be able to increase student curiosity, so that students' scientific literacy levels will be better.